N-carbobenzoxy-L-tyrosine single crystal and preparation method thereof

Through the various crystalline single crystal materials based on N-benzyloxycarbonyl-L-tyrosine, the content and distribution of water molecules are regulated, and the problem of difficulty in finely regulating water molecular assembly in the prior art is solved, efficient water molecule motion control and multiple phase transformation performance are achieved, and its application prospects in various application fields are expanded.

CN119530984APending Publication Date: 2025-02-28INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411691156.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to finely regulate the single crystal material that determines tyrosine group of water molecule assembly, and lacks materials that can effectively regulate the movement of water molecules in the crystal.

Method used

Single crystal forms of various crystal forms are prepared based on the natural tyrosine derivative N-benzyloxycarbonyl-L-tyrosine, and the content and distribution of water molecules are regulated by the tissue structure of different crystal forms, thereby obtaining supramolecular single crystals with different water content.

Benefits of technology

It has achieved simple and pure limited-domain water structure materials, enhanced the phosphorescence emission intensity of aqueous crystals, and expanded its application prospects in optical materials, phase change-induced water isotope separation materials and multi-mode phase change energy storage materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530984A_ABST
    Figure CN119530984A_ABST
Patent Text Reader

Abstract

The invention discloses a supramolecular single crystal of an amino acid derivative and a preparation method and application of the supramolecular single crystal, the supramolecular single crystal is composed of molecules as shown in a formula (1): # imgabs0 #, and x is 1 or 2. Compared with an anhydrous single crystal, the water-containing single crystal material obtained by regulating the relative content of water molecules can be reversibly converted, is low in cost, can be used as water molecule isotope separation, phosphorescence imaging and nonlinear optical carriers, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention discloses a hydrated crystal of an amino acid derivative, belonging to the technical field of materials, and relates to a single crystal form of various crystal forms based on N-benzyloxycarbonyl-L-tyrosine, and a preparation method of the various supramolecular hydrated single crystals. Background technology:

[0002] As the most widely existing compound on earth, water molecules endow hydrated assembly structures with a series of unique functions. The study of hydrated materials can not only reveal the laws of a series of physical and chemical processes involving water molecules, but also provide a theoretical basis for the design and synthesis of new water-responsive functional materials. In the natural state, almost all biochemical processes and most physical processes at room temperature and pressure involve water molecules. The participation of water molecules not only affects the physicochemical stability of crystal materials, but also endows hydrated crystal materials with new functions. Therefore, the design and development of new hydrated biological crystal materials has become an important direction for studying and regulating the physicochemical behavior of water.

[0003] The current publicly published research has generally proposed that the presence of phenolic hydroxyl groups provides abundant hydrogen bonding sites for water molecules, so using molecules containing phenolic hydroxyl groups as assembly primitives can obtain organic single crystals containing water. However, the water molecules reported in existing studies are mainly free water molecules confined in the pores of the crystal. Because of their fluidity, there has been no report on single crystal materials with a tyrosine base that can finely control the assembly of water molecules.

[0004] The present invention discloses a supramolecular single crystal with different water contents obtained by using a polymorphic single crystal based on a natural tyrosine derivative N-benzyloxycarbonyl-L-tyrosine based on the organizational structure of different crystal forms. The supramolecular single crystal based on the Z-Tyr polymorph obtained by the present invention provides a simple and pure confined water structure material through the different relative contents of water molecules in the crystal, and the material composition is simple, the material source is wide, and the cost is low. In addition, by introducing water molecules into the Z-Tyr crystal, not only the intensity of phosphorescence emission in the water-containing crystal is enhanced, but also the performance of multiple phase transitions is obtained by controlling the movement of water molecules in the crystal. The above properties enable the water-containing Z-Tyr single crystal to be used as an optical material, a water isotope separation material triggered by phase change, and a multi-mode phase change energy storage material, and has a wide range of application prospects. Summary of the invention:

[0005] The primary purpose of the present invention is to provide single crystal forms of various crystal forms based on N-benzyloxycarbonyl-L-tyrosine, and methods for preparing the various supramolecular hydrated single crystals. The prepared supramolecular N-benzyloxycarbonyl-L-tyrosine hydrated single crystals containing different equivalents of water molecules are obtained. The obtained hydrated single crystals provide a simple and pure confined water structure material.

[0006] In a first aspect, a supramolecular single crystal of an amino acid derivative is provided, wherein the supramolecular single crystal is composed of molecules as shown in formula (1): wherein x is 1 or 2.

[0007]

[0008] When x=2, the Z-Tyr·2H2O supramolecular single crystal has the following 2θ X-ray powder diffraction characteristic values:

[0009] 2θ <![CDATA[I / I0*100]]> 8.06 37.10 8.78 39.09 16.16 45.90 16.84 72.86 18.18 58.40 21.98 100.00 27.86 81.98

[0010] When x=1, the Z-Tyr·H2O supramolecular single crystal has the following 2θ X-ray powder diffraction characteristic values:

[0011]

[0012]

[0013] When x=0, the Z-Tyr supramolecular single crystal has the following 2θ X-ray powder diffraction characteristic values ​​(this crystal is used as a control):

[0014] 2θ <![CDATA[I / I0*100]]> 12.70 13.64 13.00 14.27 13.56 19.92 14.68 61.92 16.50 55.93 21.20 100 26.92 44.75

[0015] The second aspect provides a method for preparing the supramolecular single crystal as described in the first aspect, characterized in that the Z-Tyr·2H2O supramolecular single crystal is prepared by the following method: a certain amount of Z-Tyr solid powder is dissolved in anhydrous ethanol, and then an appropriate amount of ultrapure water is added to the dissolved ethanol solution to obtain a single crystal growth solution. After the single crystal growth solution is aged for a certain period of time, it is filtered to obtain a completely transparent needle-shaped crystal.

[0016] In the above preparation method, in the single crystal growth solution, the mass volume concentration of Z-Tyr is 2-100 g / L, preferably 5-50 g / L; the volume fraction of ethanol is 5-30%; and the aging time is 0.5-60 d, preferably 1-30 d.

[0017] The third aspect provides a method for preparing a Z-Tyr·H2O supramolecular single crystal. The method is characterized in that: (1) a certain amount of Z-Tyr solid powder is dissolved in anhydrous ethanol; (2) an appropriate amount of ultrapure water is added to the dissolved ethanol solution to obtain a single crystal growth solution. (3) after the single crystal growth solution is aged for a certain period of time, it is placed in a freeze dryer and dried for a certain period of time.

[0018] Wherein, the certain time is 4-72h, preferably 8-36h.

[0019] The fourth aspect provides a method for preparing a Z-Tyr supramolecular single crystal. The method is characterized in that the Z-Tyr supramolecular single crystal is prepared by the following method: a certain amount of Z-Tyr solid powder is dissolved in ultra-dry ethyl acetate, and then an appropriate amount of n-hexane is added to the dissolved ethyl acetate solution to obtain a single crystal growth solution. After the single crystal growth solution is aged for a certain period of time, it is filtered to obtain a completely transparent block crystal.

[0020] In the single crystal growth solution as described in the fourth aspect, the mass volume concentration of Z-Tyr is 5-100 g / L, preferably 10-50 g / L; the volume fraction of n-hexane is 5-50%; and the aging time is 0.5-30 d, preferably 1-10 d.

[0021] In summary, by adopting the technical scheme provided by the present invention, single crystal forms of various crystal forms based on N-benzyloxycarbonyl-L-tyrosine can be successfully obtained, and the obtained water-containing single crystal provides a simple and pure confined water structure material with simple material composition, wide material source and low cost. It has broad application prospects as a multi-mode phase change energy storage material, nonlinear optical imaging material, physical phosphorescent material and water isotope separation material. Description of the drawings:

[0022] Figure 1 This is the X-ray diffraction pattern of the Z-Tyr·2H2O supramolecular crystal prepared in Example 1.

[0023] Figure 2 This is the X-ray diffraction pattern of the Z-Tyr·H2O supramolecular crystal prepared in Example 2.

[0024] Figure 3 This is the X-ray diffraction pattern of the Z-Tyr supramolecular crystal prepared in Example 3.

[0025] Figure 4 The phosphorescence intensity diagrams of Z-Tyr·2H2O, Z-Tyr·H2O, and Z-Ty crystals prepared in Examples 1-3 indicate that the introduction of water molecules can enhance the optical properties of the crystals as phosphorescent optical materials.

[0026] Figure 5 This is the second harmonic imaging image of the Z-Tyr·2H2O crystal prepared in Example 1. The introduction of water molecules makes the crystal show a non-centrosymmetric structure, so it can be used as a nonlinear optical material.

[0027] Figure 6 This is an experiment to separate isotopic water using the Z-Tyr·H2O crystal prepared in Example 2. The isotopic selection of water molecules can be achieved by utilizing the controllable number of water molecules.

[0028] Figure 7 This is a DSC graph of multiple phase transitions exhibited by the Z-Tyr·2H2O crystal prepared in Example 1 when heated in the medium and high temperature range.

[0029] Figure 8 This is a DSC graph of the phase change of the Z-Tyr·H2O crystal prepared in Example 2 when heated in the medium and high temperature range.

[0030] Fig. 9 This is a DSC graph of the phase change of the Z-Ty crystal prepared in Example 3 when heated in the medium and high temperature range.

[0031] Fig.10 In-situ X-ray diffraction (XRD) and polarizing optical microscope (POM) images of the multiple phase transition diagrams exhibited by the Z-Tyr·2H2O crystal prepared in Example 1 when heated at different heating rates in the medium and high temperature range.

[0032] Fig.11 The in-situ X-ray diffraction (XRD) patterns of the Z-Tyr·H2O crystals prepared in Example 2 when heated at different heating rates in the medium and high temperature range.

[0033] Fig.12 The in-situ X-ray diffraction (XRD) patterns of the Z-Tyr crystal prepared in Example 3 when heated at different heating rates in the medium and high temperature range.

[0034] Fig.13 This is an in-situ Fourier transform infrared (FTIR) spectrum of the sample during the phase transition of the Z-Tyr·2H2O crystal prepared in Example 1 when heated at a rate of 1 degree Celsius per minute in the medium and high temperature range.

[0035] Fig.14 This is an in-situ Fourier transform infrared spectroscopy (FTIR) graph of the sample during the phase transition of the Z-Tyr·H2O crystal prepared in Example 2 when heated at a rate of 1 degree Celsius per minute in the medium and high temperature range.

[0036] Fig.15This is an in-situ Fourier transform infrared spectroscopy (FTIR) graph of the sample during the phase transition of the Z-Tyr crystal prepared in Example 3 when heated at a rate of 1 degree Celsius per minute in the medium and high temperature range.

[0037] Fig.16 This is an in-situ two-dimensional infrared spectrum (2D-IR) diagram of the sample during the phase transition of the Z-Tyr·2H2O crystal prepared in Example 1 when heated at a rate of 1 degree Celsius per minute in the medium and high temperature range.

[0038] Fig.17 This is an in-situ two-dimensional solid nuclear magnetic resonance (2D 13C-1H ssNMR) graph of the viscous fluid obtained when the Z-Tyr·2H2O crystal prepared in Example 1 is heated at a rate of 10 degrees Celsius per minute in the medium and high temperature range at 85 degrees Celsius.

[0039] Fig.18 This is a DSC graph of multiple phase transitions exhibited by the Z-Tyr·2H2O crystal prepared in Example 1 when heated in a low temperature range.

[0040] Fig.19 This is the DSC graph of the Z-Tyr·H2O crystal prepared in Example 2 when heated in the low temperature range.

[0041] Fig. 20 This is the DSC graph of the Z-Tyr crystal prepared in Example 3 when heated in the low temperature range.

[0042] Fig.21 The in-situ X-ray diffraction (XRD) diagrams of the multiple phase transition diagrams exhibited by the Z-Tyr·2H2O crystal prepared in Example 1 when heated at different heating rates in the low temperature range.

[0043] Fig. 22 The in-situ X-ray diffraction (XRD) patterns of the Z-Tyr·H2O crystals prepared in Example 2 when heated at different heating rates in the low temperature range.

[0044] Fig.23 In-situ X-ray diffraction (XRD) patterns of the Z-Tyr crystal prepared in Example 1 when heated at different heating rates in a low temperature range. Specific implementation method:

[0045] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme of the present invention is described in detail below through embodiments, which only describe a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present invention.

[0046] Example 1

[0047] The preparation method of dihydrated Z-Tyr·2H2O supramolecular crystal comprises the following steps:

[0048] (1) Weigh 10 g of Z-Tyr, add 100 mL of anhydrous ethanol and dissolve by ultrasonication to obtain a clear and transparent Z-Tyr solution;

[0049] (2) adding 900 mL of deionized water to the solution obtained in the previous step to obtain a milky white emulsion through a liquid-liquid phase separation process;

[0050] (3) After the dispersion obtained in the previous step is aged for 1 day, it is filtered to obtain needle-shaped transparent crystals.

[0051] Figure 1 This is the X-ray diffraction pattern of the Z-Tyr·2H2O supramolecular crystal prepared in Example 1.

[0052] Example 2

[0053] The preparation method of monohydrate Z-Tyr·H2O supramolecular crystal comprises the following steps:

[0054] (1) The Z-Tyr raw material is fully ground, and then water is added for further ultrasonic dispersion to obtain a uniform dispersion liquid, wherein the concentration of the raw material in the dispersion liquid is 10 mg / mL;

[0055] (2) adding 900 mL of deionized water to the solution obtained in the previous step to obtain a milky white emulsion through a liquid-liquid phase separation process;

[0056] (3) The emulsion is aged for 1 day to obtain Z-Tyr·2H2O crystals.

[0057] (4) After the Z-Tyr·2H2O crystals have been obtained, they are frozen together with the growth solution in a -80°C refrigerator;

[0058] (5) Freeze-dry the completely frozen sample in a vacuum dryer for no less than 36 h;

[0059] (6) The freeze-dried sample is slowly restored to room temperature to obtain a transparent needle-shaped sample.

[0060] Figure 2 This is the X-ray diffraction pattern of the Z-Tyr·H2O crystal type crystal prepared in Example 2.

[0061] Example 3 (control group)

[0062] The preparation method of anhydrous Z-Tyr crystal single crystal comprises the following steps:

[0063] (1) Weigh 10 mg of Z-Tyr, add 100 μL of anhydrous ethyl acetate and dissolve by ultrasonication to obtain a clear and transparent Z-Tyr solution;

[0064] (2) Add 900 μL of n-hexane to the solution obtained in the previous step to prepare a growth solution;

[0065] (3) The above growth solution is left to stand at room temperature for 7 days, after which transparent block crystals will be obtained.

[0066] Figure 3 This is the X-ray diffraction pattern of the Z-Tyr crystal type prepared in Example 3.

[0067] Example 4

[0068] The preparation method of Z-Tyr·2H2O supramolecular crystal comprises the following steps:

[0069] (1) Weigh 100 g of Z-Tyr, add 100 mL of anhydrous ethanol and dissolve by ultrasonication to obtain a clear and transparent Z-Tyr solution;

[0070] (2) adding 900 mL of deionized water to the solution obtained in the previous step to obtain a milky white emulsion through a liquid-liquid phase separation process;

[0071] (3) After the dispersion obtained in the previous step is aged for 0.5 days, it is filtered to obtain needle-shaped transparent crystals.

[0072] Example 5

[0073] The preparation method of Z-Tyr·2H2O supramolecular crystal comprises the following steps:

[0074] (1) Weigh 2 g of Z-Tyr and add it into 300 mL of anhydrous ethanol for ultrasonic dissolution to obtain a clear and transparent Z-Tyr solution;

[0075] (2) adding 700 mL of deionized water to the solution obtained in the previous step to obtain a milky white emulsion through a liquid-liquid phase separation process;

[0076] (3) After the dispersion obtained in the previous step is aged for 10 days, it is filtered to obtain needle-shaped transparent crystals.

[0077] Example 6

[0078] The preparation method of Z-Tyr·2H2O supramolecular crystal comprises the following steps:

[0079] (1) Weigh 10 g of Z-Tyr and add it into 200 mL of anhydrous ethanol for ultrasonic dissolution to obtain a clear and transparent Z-Tyr solution;

[0080] (2) adding 800 mL of deionized water to the solution obtained in the previous step to obtain a milky white emulsion through a liquid-liquid phase separation process;

[0081] (3) After the dispersion obtained in the previous step is aged for 7 days, it is filtered to obtain needle-shaped transparent crystals.

[0082] Example 7

[0083] The preparation method of Z-Tyr·H2O supramolecular crystal comprises the following steps:

[0084] (1) The Z-Tyr raw material is fully ground, and then water is added for further ultrasonic dispersion to obtain a uniform dispersion liquid, wherein the concentration of the raw material in the dispersion liquid is 10 mg / mL;

[0085] (2) adding 900 mL of deionized water to the solution obtained in the previous step to obtain a milky white emulsion through a liquid-liquid phase separation process;

[0086] (3) The emulsion is aged for 1 day to obtain Z-Tyr·2H2O crystals.

[0087] (4) After the Z-Tyr·2H2O crystals have been obtained, they are frozen together with the growth solution in a -80°C refrigerator;

[0088] (5) The completely frozen sample was freeze-dried in a vacuum dryer for 8 h;

[0089] (6) The freeze-dried sample is slowly restored to room temperature to obtain a transparent needle-shaped sample.

[0090] Example 8

[0091] The preparation method of Z-Tyr·H2O supramolecular crystal comprises the following steps:

[0092] (1) The Z-Tyr raw material is fully ground, and then water is added for further ultrasonic dispersion to obtain a uniform dispersion liquid, wherein the concentration of the raw material in the dispersion liquid is 10 mg / mL;

[0093] (2) adding 900 mL of deionized water to the solution obtained in the previous step to obtain a milky white emulsion through a liquid-liquid phase separation process;

[0094] (3) The emulsion is aged for 1 day to obtain Z-Tyr·2H2O crystals.

[0095] (4) After the Z-Tyr·2H2O crystals have been obtained, they are frozen together with the growth solution in a -80°C refrigerator;

[0096] (5) Freeze-dry the completely frozen sample in a vacuum dryer for 24 h;

[0097] (6) The freeze-dried sample is slowly restored to room temperature to obtain a transparent needle-shaped sample.

[0098] Example 9

[0099] The preparation method of Z-Tyr crystal type single crystal comprises the following steps:

[0100] (1) Weigh 100 mg of Z-Tyr and add 50 μL of anhydrous ethyl acetate to dissolve it by ultrasonication to obtain a clear and transparent Z-Tyr solution;

[0101] (2) adding 950 μL of n-hexane to the solution obtained in the previous step to obtain a milky white emulsion through a liquid-liquid phase separation process;

[0102] (3) The above emulsion is allowed to stand at room temperature for 1 day, after which transparent block crystals are obtained.

[0103] Example 10

[0104] The preparation method of Z-Tyr crystal type single crystal comprises the following steps:

[0105] (1) Weigh 10 mg of Z-Tyr, add 500 μL of anhydrous ethyl acetate and dissolve by ultrasonication to obtain a clear and transparent Z-Tyr solution;

[0106] (2) Add 900 μL of n-hexane to the solution obtained in the previous step to prepare a growth solution;

[0107] (3) The above growth solution is left to stand at room temperature for 7 days, after which transparent block crystals will be obtained.

[0108] Embodiment 11

[0109] The influence of the relative content of water molecules in different Z-Tyr crystals on the room temperature phosphorescence intensity of the crystals:

[0110] (1) Single crystals of Z-Tyr·2H2O, Z-Tyr·H2O and Z-Tyr with different water contents were prepared respectively according to the methods of Examples 1-3;

[0111] (2) Weigh three crystals of equal mass at room temperature as samples to be tested;

[0112] (3) The single crystal sample obtained in the previous step is placed at room temperature, using 365 nm light as the excitation light, to test the steady-state phosphorescence spectrum of the sample and obtain the phosphorescence intensity.

[0113] Figure 4The phosphorescence intensity diagrams of Z-Tyr·2H2O, Z-Tyr·H2O, and Z-Ty crystals prepared in Examples 1-3 indicate that the introduction of twice the molar amount of water molecules can enhance the optical properties of the crystals as phosphorescent optical materials.

[0114] Example 12

[0115] The introduction of water molecules leads to second harmonic imaging of Z-Tyr·2H2O single crystal:

[0116] (1) preparing Z-Tyr·2H2O single crystals respectively according to the method of Example 1;

[0117] (2) Pick out the needle-shaped crystals using a sampling needle and place them on a smooth and clean quartz slide;

[0118] (3) Using a pump laser as the incident light, avalanche detection is used to detect the fluorescence signal at the frequency doubled of the incident light.

[0119] Figure 5 This is the second harmonic imaging image of the Z-Tyr·2H2O crystal prepared in Example 1. The introduction of twice the molar amount of water molecules makes the Z-Tyr crystal skeleton show a non-centrosymmetric structure. Therefore, the existence of this structure makes the Z-Tyr·2H2O crystal can be used as a nonlinear optical material.

[0120] Embodiment 13

[0121] Monohydrate Z-Tyr·H2O single crystal for the purification of water molecule isotopes:

[0122] (1) preparing Z-Tyr·H2O single crystals respectively according to the method of Example 2;

[0123] (2) Weigh 2 g of the Z-Tyr·H2O single crystal obtained in the previous step, place it in a glove box, and exchange it for one week to remove the water molecule layer adsorbed on the surface of the crystal;

[0124] (3) 5 mL of 95% pure heavy water was added to the prepared Z-Tyr·H2O single crystal and allowed to stand for one week. The purity of the heavy water was then increased to 96.3% by nuclear magnetic resonance measurement.

[0125] Figure 6 This is an experiment to separate isotopic water using the Z-Tyr·H2O crystal prepared in Example 2. The isotopic selection of water molecules can be achieved by utilizing the controllable number of water molecules.

[0126] Embodiment 14

[0127] The DSC spectrum shows the multimodal phase transition behavior of Z-Tyr·2H2O single crystal in the medium and high temperature range affected by the heating rate, which is caused by the movement of water molecules in the crystal:

[0128] (1) preparing Z-Tyr·2H2O single crystals respectively according to the method of Example 1;

[0129] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0130] (3) Weigh the mass of the air-dried crystals using a precision balance;

[0131] (4) The air-dried sample was placed in a crucible made of alumina and tested. The test temperature range was from 0 degrees Celsius to 120 degrees Celsius, and the heating rates were 1 degree Celsius per minute, 2 degrees Celsius per minute, 5 degrees Celsius per minute, 10 degrees Celsius per minute and 15 degrees Celsius per minute.

[0132] Figure 7 This is a DSC graph of the multiple phase transition diagram of the Z-Tyr·2H2O crystal prepared in Example 1 when heated in the medium and high temperature range. This graph confirms that with the introduction of twice the molar amount of water molecules, the entire two-hydrate crystal (Z-Tyr·2H2O) has more phase transition points than the monohydrate crystal (Z-Tyr·H2O) and the anhydrate crystal (Z-Tyr). Therefore, the phase transition behavior is regulated by the change of the self-assembly structure of water molecules in the crystal.

[0133] Embodiment 15

[0134] The changes in XRD spectra and polarized images confirm the multimodal phase transition of Z-Tyr·2H2O single crystals caused by the movement of water molecules on the six-membered ring affected by the heating rate:

[0135] (1) preparing Z-Tyr·2H2O single crystals respectively according to the method of Example 1;

[0136] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0137] (3) Place the air-dried sample into an in-situ variable temperature test sample stage for testing. The test temperature range is from 0°C to 120°C, the heating rate is 1°C per minute and 15°C per minute, the scanning step is 1°, and the test angle range is 5-45°.

[0138] (4) At the same time, the air-dried single crystal obtained in (2) was placed on a hot stage of a polarizing microscope. The test temperature range was controlled from 0°C to 120°C, and the heating rates were 1°C per minute and 15°C per minute, respectively. The morphological changes of the sample were observed in situ.

[0139] Fig.10 The in-situ X-ray diffraction (XRD) and polarizing microscope (POM) images of the multiple phase transition diagrams of the Z-Tyr·2H2O crystals prepared in Example 1 when heated at different heating rates in the medium and high temperature range. The above data graphs confirm that the structural transformation in the dihydrate crystal (Z-Tyr·2H2O) is a change behavior that responds to the crystal heating rate. When the temperature is rapidly increased, the dihydrate crystal (Z-Tyr·2H2O) directly changes from a crystalline state to an amorphous state; when heated slowly, the crystal will appear in an amorphous state of solid-solid transition and then transform into a monohydrate crystal (Z-Tyr·H2O), which is a transition from a crystalline state to a crystalline state.

[0140] Example 16

[0141] The changes in infrared spectra confirmed the solid-solid phase transition of Z-Tyr·2H2O single crystals caused by the movement of water molecules in the crystal during the slow heating process:

[0142] (1) preparing Z-Tyr·2H2O single crystals respectively according to the method of Example 1;

[0143] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0144] (3) Grind the air-dried sample and dry potassium bromide and press into tablets;

[0145] (4) The sample was placed on a temperature-controlled hot plate, and the test temperature range was controlled from 25°C to 85°C, with a heating rate of 1°C per minute. The FTIR and 2D-IR peak changes of the sample were observed in situ.

[0146] Fig.13 This is an in-situ Fourier transform infrared (FTIR) spectrum of the sample during the phase transition of the Z-Tyr·2H2O crystal prepared in Example 1 when heated at a rate of 1 degree Celsius per minute in the medium and high temperature range.

[0147] Fig.16 This is an in-situ two-dimensional infrared spectrum (2D-IR) diagram of the sample during the phase transition of the Z-Tyr·2H2O crystal prepared in Example 1 when heated at a rate of 1 degree Celsius per minute in the medium and high temperature range. Fig.13 and Fig.14 , Fig.15 The comparison shows that the dihydrate crystal (Z-Tyr·2H2O) has a peak at 2954 cm -1 The infrared absorption peak at is attributed to the asymmetric stretching vibration of the hydrated phenolic hydroxyl groups. During the phase transition, the displacement of this absorption peak changes significantly, which means that the phase transition in the entire medium and high temperature range is driven by the rearrangement of the self-assembled structure of the phenolic hydroxyl groups themselves.

[0148] Embodiment 17

[0149] Characterization of the interaction forces in Z-Tyr·2H2O viscous fluid obtained by the movement of water molecules in the crystal:

[0150] (1) preparing Z-Tyr·2H2O single crystals respectively according to the method of Example 1;

[0151] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0152] (3) Place the air-dried sample in a 7 mm diameter zirconium oxide solid NMR sample tube, fill and press tightly;

[0153] (4) Control the heating component and control the test temperature range to be directly heated from 25 degrees Celsius to 85 degrees Celsius, with a heating rate of 10 degrees Celsius per minute and a rotation speed of 8000 revolutions. Use the NOE enhanced sampling method to determine the coupling effect between hydrocarbons in the viscous fluid.

[0154] Fig.17 The Z-Tyr·2H2O crystal prepared in Example 1 was heated at a rate of 10 degrees Celsius per minute in the medium and high temperature range. At 85 degrees Celsius, the in-situ two-dimensional solid-state nuclear magnetic resonance (2D) 13 C- 1 H ssNMR) graph.

[0155] Embodiment 18

[0156] The DSC spectrum shows the multimodal phase transition behavior of Z-Tyr·2H2O single crystal in the medium and high temperature range affected by the heating rate, which is caused by the movement of water molecules in the crystal:

[0157] (1) preparing Z-Tyr·2H2O single crystals respectively according to the method of Example 1;

[0158] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0159] (3) Weigh the mass of the air-dried crystals using a precision balance;

[0160] (4) The air-dried sample was placed in a crucible made of aluminum oxide and tested in a temperature range from -100 degrees Celsius to 0 degrees Celsius at a heating rate of 10 degrees Celsius per minute.

[0161] Fig.18This is a DSC graph of multiple phase transitions of the Z-Tyr·2H2O crystal prepared in Example 1 when heated in a low temperature range. Fig.18 and Fig.19 It can be seen from the comparison that only the two hydrated single crystals (Z-Tyr·2H2O) undergo phase transition in the low temperature region, so the phase transition in the low temperature section can only come from the structural transformation of water molecules in the Z-Tyr crystal framework. And it is worth noting that the first phase transition point (-77℃) is extremely close to the temperature point of the protein dynamic transition in nature (-73℃). Therefore, revealing the low-temperature phase transition of two hydrated crystals is of great significance for understanding the inherent properties of life systems.

[0162] Embodiment 19

[0163] The phase transition of ZY-2H2O single crystal in the low temperature range caused by the movement of water molecules on the six-membered ring is confirmed by the change of XRD:

[0164] (1) preparing ZY-2H2O single crystals respectively according to the method of Example 1;

[0165] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0166] (3) Place the air-dried sample into an in-situ variable temperature test sample stage for testing. The test temperature range is from -100 degrees Celsius to 0 degrees Celsius, the heating rate is 10 degrees Celsius per minute, the scanning step is 1°, and the test angle range is 5-45°.

[0167] Fig.21 This is an in-situ X-ray diffraction (XRD) diagram of the multiple phase transition diagram exhibited by the ZY-2H2O crystal prepared in Example 1 when heated in a low temperature range.

[0168] Embodiment 20

[0169] Phase transition of Z-Tyr·H2O single crystal at different heating rates in the medium and high temperature range:

[0170] (1) preparing Z-Tyr·H2O single crystals respectively according to the method of Example 2;

[0171] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0172] (3) Weigh the mass of the air-dried crystals using a precision balance;

[0173] (4) The air-dried sample was placed in a crucible made of alumina and tested. The test temperature range was from 0°C to 150°C, and the heating rates were 2°C per minute, 10°C per minute, and 15°C per minute.

[0174] Figure 8 This is a DSC graph of the phase change of the Z-Tyr·H2O crystal prepared in Example 2 when heated in the medium and high temperature range.

[0175] Embodiment 21

[0176] Phase transition of Z-Tyr single crystal at different heating rates in the medium and high temperature range:

[0177] (1) preparing Z-Tyr single crystals respectively according to the method of Example 3;

[0178] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0179] (3) Weigh the mass of the air-dried crystals using a precision balance;

[0180] (4) The air-dried sample was placed in a crucible made of alumina and tested. The test temperature range was from 0°C to 150°C, and the heating rates were 2°C per minute, 10°C per minute, and 15°C per minute.

[0181] Fig. 9 This is a DSC graph of the phase change of the Z-Tyr crystal prepared in Example 3 when heated in the medium and high temperature range.

[0182] Embodiment 22

[0183] XRD spectra of phase transition behavior of Z-Tyr·H2O single crystal at different heating rates in the medium and high temperature range:

[0184] (1) preparing Z-Tyr·H2O single crystals respectively according to the method of Example 2;

[0185] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0186] (3) Place the air-dried sample into an in-situ variable temperature test sample stage for testing. The test temperature range is from 0°C to 125°C, the heating rate is 1°C per minute and 15°C per minute, the scanning step is 1°, and the test angle range is 5-45°;

[0187] Fig.11The in-situ X-ray diffraction (XRD) patterns of the Z-Tyr·H2O crystals prepared in Example 2 when heated at different heating rates in the medium and high temperature range.

[0188] Embodiment 23

[0189] XRD spectra of phase transition behavior of Z-Tyr single crystal at different heating rates in the medium and high temperature range:

[0190] (1) preparing Z-Tyr single crystals respectively according to the method of Example 3;

[0191] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0192] (3) Place the air-dried sample into an in-situ variable temperature test sample stage for testing. The test temperature range is from 0°C to 125°C, the heating rate is 1°C per minute and 15°C per minute, the scanning step is 1°, and the test angle range is 5-45°;

[0193] Fig.12 The in-situ X-ray diffraction (XRD) patterns of the Z-Tyr crystal prepared in Example 3 when heated at different heating rates in the medium and high temperature range.

[0194] Embodiment 24

[0195] Changes in the infrared spectrum of Z-Tyr·H2O single crystal during slow heating:

[0196] (1) preparing Z-Tyr·H2O single crystals respectively according to the method of Example 2;

[0197] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0198] (3) Grind the air-dried sample and dry potassium bromide and press into tablets;

[0199] (4) Place the sample on a temperature-controlled hot plate, control the test temperature range from 25°C to 85°C, and increase the temperature at a rate of 1°C per minute. Observe the changes in the FTIR spectrum peak of the sample in situ.

[0200] Fig.14 This is an in-situ Fourier transform infrared spectroscopy (FTIR) graph of the sample during the phase transition of the Z-Tyr·H2O crystal prepared in Example 2 when heated at a rate of 1 degree Celsius per minute in the medium and high temperature range.

[0201] Embodiment 25

[0202] Changes in the infrared spectrum of Z-Tyr single crystal during slow heating:

[0203] (1) preparing Z-Tyr single crystals respectively according to the method of Example 3;

[0204] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0205] (3) Grind the air-dried sample and dry potassium bromide and press into tablets;

[0206] (4) Place the sample on a temperature-controlled hot plate, control the test temperature range from 25°C to 85°C, and increase the temperature at a rate of 1°C per minute. Observe the changes in the FTIR spectrum peak of the sample in situ.

[0207] Fig.15 This is an in-situ Fourier transform infrared spectroscopy (FTIR) graph of the sample during the phase transition of the Z-Tyr crystal prepared in Example 3 when heated at a rate of 1 degree Celsius per minute in the medium and high temperature range.

[0208] Embodiment 26

[0209] Phase transition of Z-Tyr·H2O single crystal at different heating rates in the low temperature range:

[0210] (1) preparing Z-Tyr·H2O single crystals respectively according to the method of Example 2;

[0211] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0212] (3) Weigh the mass of the air-dried crystals using a precision balance;

[0213] (4) The air-dried sample was placed in a crucible made of aluminum oxide and tested in a temperature range from -100 degrees Celsius to 0 degrees Celsius at a heating rate of 10 degrees Celsius per minute.

[0214] Fig.19 This is the DSC graph of the Z-Tyr·H2O crystal prepared in Example 2 when heated in the low temperature range.

[0215] Embodiment 27

[0216] Phase transition of Z-Tyr single crystal at different heating rates in the low temperature range:

[0217] (1) preparing Z-Tyr single crystals respectively according to the method of Example 3;

[0218] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0219] (3) Weigh the mass of the air-dried crystals using a precision balance;

[0220] (4) The air-dried sample was placed in a crucible made of aluminum oxide and tested in a temperature range from -100 degrees Celsius to 0 degrees Celsius at a heating rate of 10 degrees Celsius per minute.

[0221] Fig. 20 This is the DSC graph of the Z-Tyr crystal prepared in Example 3 when heated in the low temperature range.

[0222] Embodiment 28

[0223] XRD spectra of phase transition behavior of Z-Tyr·H2O single crystal at different heating rates in the medium and high temperature range:

[0224] (1) preparing Z-Tyr·H2O single crystals respectively according to the method of Example 2;

[0225] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0226] (3) Place the air-dried sample into an in-situ variable temperature test sample stage for testing. The test temperature range is from -100 degrees Celsius to 0 degrees Celsius, the heating rate is 10 degrees Celsius per minute, the scanning step is 1°, and the test angle range is 5-45°;

[0227] Fig. 22 The in-situ X-ray diffraction (XRD) patterns of the Z-Tyr·H2O crystals prepared in Example 2 when heated at different heating rates in the low temperature range.

[0228] Embodiment 29

[0229] XRD spectra of phase transition behavior of Z-Tyr single crystal at different heating rates in the medium and high temperature range:

[0230] (1) preparing Z-Tyr single crystals respectively according to the method of Example 3;

[0231] (2) Pick out the needle-shaped crystals using a sampling needle, place them on a smooth and clean quartz slide and air-dry them to remove surface water molecules;

[0232] (3) Place the air-dried sample into an in-situ variable temperature test sample stage for testing. The test temperature range is from -100 degrees Celsius to 0 degrees Celsius, the heating rate is 10 degrees Celsius per minute, the scanning step is 1°, and the test angle range is 5-45°;

[0233] Fig.23 The in-situ X-ray diffraction (XRD) patterns of the Z-Tyr crystal prepared in Example 3 when heated at different heating rates in the low temperature range.

Claims

1. A single crystal of an amino acid derivative, characterized in that: The single crystal is composed of molecules as shown in formula (1): Where x is 1 or 2.

2. The single crystal according to claim 1, characterized in that When x=2, the Z-Tyr·2H2O supramolecular single crystal has the following 2θ X-ray powder diffraction characteristic values: 。 3. The single crystal according to claim 1, characterized in that When x=1, the Z-Tyr·H2O supramolecular single crystal has the following 2θ X-ray powder diffraction characteristic values: 。 4. The method for preparing a single crystal according to claim 2, characterized in that: The method comprises the following steps: (1) dissolving Z-Tyr solid powder in anhydrous ethanol; (2) adding ultrapure water to the dissolved ethanol solution to obtain a single crystal growth solution; and (3) aging the single crystal growth solution and filtering to obtain needle-shaped crystals.

5. The method for preparing a single crystal according to claim 4, characterized in that: In the single crystal growth solution of step (2), the mass volume concentration of Z-Tyr is 2-100 g / L, preferably 5-50 g / L; the volume fraction of ethanol is 5-30%; the aging time of step (3) is 0.5-60 days, preferably 1-30 days.

6. The method for preparing a single crystal according to claim 3, characterized in that: The method comprises the following steps: (1) dissolving a certain amount of Z-Tyr solid powder in anhydrous ethanol; (2) adding an appropriate amount of ultrapure water to the dissolved ethanol solution to obtain a single crystal growth solution; and (3) after the single crystal growth solution is aged for a certain period of time, placing it in a freeze dryer and drying it for a certain period of time.

7. The method for preparing a single crystal according to claim 6, characterized in that: The certain period of time is 4-72 hours, preferably 8-36 hours.

8. Use of the single crystal according to any one of claims 1 to 3 as a multi-mode phase change material, a nonlinear optical imaging material, a physical phosphorescent material, or a water isotope separation material.

9. Use of the single crystal according to claim 2 as a phosphorescent material.

10. Use of the single crystal according to claim 3 as a water isotope separation material.